Individualized management of polycystic ovary syndrome - Morshed, Md Shahed (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrinopathy that remains mysterious. The heterogeneous presentations underscore the limitations of a standardized, ‘one size fits all’ management strategy. Hence, the management of PCOS is essentially symptomatic and individualized. Lifestyle management always remains central. The patient’s stages of life, fertility issues, as well as metabolic factors are principal factors in determining individual management. Besides the patient’s comorbidity, the availability of drugs and tolerability also affect the choice of treatment. The individualization is now exploring the pharmacogenomics of individual drugs. In this presentation, a few cases will be discussed to demonstrate the individualized approach. By moving beyond a singular treatment algorithm, we can provide more effective, compassionate, and holistic care for individuals with PCOS. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S15]